COMPARISON OF ZOOGEOGRAPHY AMONG RATS, FRUIT BATS AND INSECTIVOROUS BATS ON INDONESIAN ISLANDS - Ibnu Maryanto; Seigo Higashi (BRIN Publishing (Penerbit BRIN), 2011)
The species number of rat, fruit bat, and insectivorous bat was signifi-cantly correlated with island size when five major islands of Irian, Borneo, Su-matra, Sulawesi and Java were included in the analysis, and the z area values were 0.22; 0.19 and, 0.26, respectively. When these islands were excluded, the correlation between species richness and island size was significant in fruit bats and insectivorous bats (R2=0.31, P<0.01) but not in rats. Z value declined to 0.07 in rats, 0.14 in fruit bats and 0.19 in insectivorous bats. Zoogeographic bounda-ries are shown. Wallace’s Line seems to be a zoogeographic boundary for all of three mammal groups; Bali and Lombok Islands belong to the cluster of Lesser Sunda in rats but not to the cluster of Greater Sunda in bats. Although Weber’s Line also seems to be a zoogeographic boundary for all of the three mammal groups, an effective boundary lies between Sulawesi and Maluku in rats and in-sectivorous bats but not between northern Maluku and Irian in fruit bats. The fauna of fruit bats in Southern Maluku is more similar to those of Irian. Lydek-ker’s line seems to be a boundary for only rats, though Biak, Owi and Yapen Islands belong to the cluster of Maluku. In addition to those boundaries, Cluster analyses revealed another boundary for rats between Sumatra and western Su-matra islands (Mentawai Islands) and between Lesser Sunda and Sulawesi to Southern Maluku for fruit and insectivorous bats.